2014
DOI: 10.1097/iae.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal Proliferation Seen in Association With Lamellar Macular Holes

Abstract: Spectral domain optical coherence tomography imaging showed that a subset of patients with LMH had an epiretinal proliferation with medium reflectivity and no evidence of contractile properties that was contiguous with layers of the mid-retina. This phenotype differs from conventionally described ERMs in appearance and induced changes of the underlying retina. Given these distinct anatomical relationships, the presence of LHEP could affect surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
255
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(278 citation statements)
references
References 25 publications
18
255
1
4
Order By: Relevance
“…Thus, peeling of LHEP might be not as important for relieving epiretinal traction as peeling a standard ERM, but it would have the function of allowing surgical access to the ILM. The role of ILM as epiretinal material exerting traction in association with LMHs seems to be also confirmed by the fact that, as reported by previous studies, 5,12 and as observed in this series, full-thickness macular holes evolved from LMHs and associated with LHEP generally close after surgical removal of ILM.…”
Section: In This Retrospective Study We Show That In Eyessupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, peeling of LHEP might be not as important for relieving epiretinal traction as peeling a standard ERM, but it would have the function of allowing surgical access to the ILM. The role of ILM as epiretinal material exerting traction in association with LMHs seems to be also confirmed by the fact that, as reported by previous studies, 5,12 and as observed in this series, full-thickness macular holes evolved from LMHs and associated with LHEP generally close after surgical removal of ILM.…”
Section: In This Retrospective Study We Show That In Eyessupporting
confidence: 90%
“…5 To be included in the study, the eyes must also present an area of increased autofluorescent signal that colocalized with the inner defect observed in the fovea and was not attributable to an intraretinal cyst based on OCT images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 We did not observe any cases of VMT associated with the recently described entity of lamellar hole-associated epiretinal proliferation. 26 Although the shape of the fovea is currently not known to be a prognostic factor, it is important in distinguishing VMT from VMA and correlates with the width of adhesion and elevation to suggest the extent of traction. In this study, we subclassified shape into normal, loss of inner retinal profile, or eversion of fovea.…”
Section: Figure 1 Schematic Representation Of the Focal Vmt Classificmentioning
confidence: 99%